Saving on clay: the Linear B practice of cutting tablets - Tomas, Helena (Array, 2013)
The practice of cutting clay tablets is evident in both Minoan Linear A and Mycenaean Linear B administration. Tablets were most probably cut after having been inscribed, when the residue of clay with no text was removed, either to be reused for producing further tablets, or to minimize space needed for their storage. This habit is especially apparent in the earliest deposit of Linear B tablets – the Room of the Chariot Tablets – where nearly 20% of all tablets were cut. It is precisely these tablets that will discussed in this paper. Most of the cut tablets from the Room of the Chariot Tablets are of elongated shape. Some were cut on the sides immediately before the first sign or immediately after the last one. This may reflect the practice of saving clay whenever possible. The tablets generally give an impression of economy: their entire surface is usually inscribed, without leaving any unused space ; when a tablet was larger than needed, the needless parts seem to have been excised and reused. Another explanation has been proposed for the cutting of these tablets: the practice of dividing a set of information into separate records. Although cut and separated in the past, scholars recently joined some of these tablets proving that these small documents initially belonged to one larger tablet. The name introduced to describe this kind of a document is a simili-join. As for the purpose of simili-joins, it has been previously suggested that larger tablets were divided into smaller units for the purpose of rearranging the information, and this is a possibility that is further explored in this paper. Apart from the actual cutting, another feature may be an indication of the practice of simili-joins. A certain number of elongated tablets from the Room of the Chariot tablets have vertical lines incised across them. It seems that their function was to divide certain sections of a tablet. Perhaps these lines were incised to indicate where to cut the tablet, as suggested by J. Driessen. By following this line of thought, it will be proposed that records of this type were probably written with the anticipated need for rearranging of the data, meaning that the simili-joins may have been planned in advance. Hence the practice of marking tablets with vertical lines for cutting. These lines must have been incised when the tablet was still moist, i.e. either while inscribing the text, or not much longer afterwards. If so, the question is: why did such tablets remain undivided?